DIGITAL TRANSFORMATION AND READINESS OF PUBLIC ELEMENTARY SCHOOL TEACHERS IN THE DISTRICT OF SIGMA - Lorca, Jonna (President University, 2025)
The study investigated the level of digital transformation of schools and degree of digital readiness of teachers in the District of Sigma. The respondents of the study were 174 randomly selected elementary school teachers in the District of Sigma. The study used the descriptive-correlational research design. Data were collected using a validated and reliability-tested researcher-made questionnaire. Statistical tools used to analyze and interpret data were frequency count, percentage, mean, t-test, and analysis of variance, and Pearson r. The results revealed that the level of digital transformation of schools was high and the degree of digital readiness of teachers was to a certain extent. There was no significant difference in the digital transformation of schools as perceived by the teachers when they were grouped according to gender, age, highest educational attainment, number of years in service and monthly income. Moreover, there was no significant difference the degree of digital readiness of teachers when they were grouped according to gender, age, highest educational attainment, number of years in service and monthly income. The digital transformation of schools was found to be significantly associated with the digital readiness of teachers. The result indicated that the more digitally ready are the teachers, the more they will utilize their digital abilities in their classes. Hence, the school needs to provide them with the needed facilities like equipment, connectivity and instructional materials. Digitally ready educators perceive technology for all of its innovative potential, rather than something they are required to do in a step-by-step manner.Â